Literature Review: Pengaruh Peran Audit Internal , Sistem Pengendalian Internal dan Audit Manajemen Terhadap Good Corporate Governance (GCG) pada Badan Usaha Milik Negara di Indonesia - Harahap, Aulia Rahman (Universitas Harapan Medan, 2023)
This research aims to review literature regarding the influence of internal audits, internal control systems, and management audits on the implementation of good corporate governance (GCG) in State-Owned Enterprises (BUMN). Internal audit serves as an independent oversight mechanism that ensures operational integrity and regulatory compliance. An effective internal control system plays a crucial role in identifying and managing risks, as well as ensuring the accuracy of financial reporting. Management audits, which assess operational efficiency and effectiveness, provide recommendations for continuous improvement. Through this literature review, it was found that these three elements interact with each other to create a strong control environment, increase transparency, and strengthen accountability in the management of BUMN. It is hoped that the results of this study will provide insight for practitioners and researchers in understanding the importance of implementing good audit and internal control in order to achieve optimal corporate governance.